A framework for linking forestry co-management institutional arrangements with their associated livelihood outcomes. (October 2016) - Ming'ate, Felix Lamech Mogambi
Co-management of forest resources has gained acceptance among governments, development agencies and development practitioners as an alternative natural resources management strategy to the top-down or centralized government management approach. However, a significant methodological issue in the current literature on evaluation of co-management institutional arrangement is how to link these institutions with sustainable livelihood outcomes of the poor forest dependent communities. To address this limitation, there is need for linking co-management with the sustainability of the community, effectively for the sustainability of its livelihood. This article links two theoretical concepts—co-management and sustainable livelihood approach (SLA)—to formulate an evaluative framework for co-management of forest institutions and their associated livelihood outcomes.